2012
DOI: 10.1289/ehp.1003169
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Acute Respiratory Response in a Panel of Asthmatic Children along the U.S.–Mexico Border

Abstract: Background: Concerns regarding the health impact of urban air pollution on asthmatic children are pronounced along the U.S.–Mexico border because of rapid population growth near busy border highways and roads.Objectives: We conducted the first binational study of the impacts of air pollution on asthmatic children in Ciudad Juarez, Mexico, and El Paso, Texas, USA, and compared different exposure metrics to assess acute respiratory response.Methods: We recruited 58 asthmatic children from two schools in Ciudad J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 22 publications
4
44
0
1
Order By: Relevance
“…43 Another cohort panel study at the US–Mexico border towns of Ciudad Juarez, Mexico, and El Paso, Texas, found positive associations between FE NO in children with asthma and both black carbon and PM 2.5 measurements at school sites. 44 Our null PM 2.5 results were consistent with a longitudinal study of FE NO in children with asthma in Windsor, Canada, with lower levels of PM 2.5 (median 6.5 μ g/m 3 ). 45 The Canadian study instead found a positive association between a biomarker of oxidative stress in exhaled breath condensates and both PM 2.5 and NO 2 .…”
Section: Discussionsupporting
confidence: 88%
“…43 Another cohort panel study at the US–Mexico border towns of Ciudad Juarez, Mexico, and El Paso, Texas, found positive associations between FE NO in children with asthma and both black carbon and PM 2.5 measurements at school sites. 44 Our null PM 2.5 results were consistent with a longitudinal study of FE NO in children with asthma in Windsor, Canada, with lower levels of PM 2.5 (median 6.5 μ g/m 3 ). 45 The Canadian study instead found a positive association between a biomarker of oxidative stress in exhaled breath condensates and both PM 2.5 and NO 2 .…”
Section: Discussionsupporting
confidence: 88%
“…El Paso County had a lower median household income (2011 US $36,333) than the State of Texas (2011 US $49,391) and the US (2011 US $50,502) with a poverty rate of 24%, which was higher than the national rate (16%). In previous studies in this city, researchers have found relatively modest associations between air pollutants (including PM 2.5 ) and respiratory health effects (Grineski, et al, 2011; Sarnat et al, 2011; Svendsen et al, 2012; Zora et al, 2013). …”
Section: Methodsmentioning
confidence: 83%
“…Given the relatively short follow-up period for this study, however, inferences relating to the temporality of any of the endpoints should be viewed cautiously. Numerous studies have reported associations between air pollution and acute eNO response utilizing panel based designs (Adamkiewicz et al, 2004; Buonanno et al, 2013; Delfino et al, 2006; Greenwald et al, 2013; Sarnat et al, 2012). …”
Section: Discussionmentioning
confidence: 99%